Differential Display Probes for cDNA Arrays - Thomas Trenkle; John Welsh; Michael McClelland (BioTechniques)
PCR with a combination of one arbitrary and one oligo(dT) anchor primer can be used to generate an effective probe for cDNA arrays. The method uses less than 1/200 of the amount of RNA used in some other array hybridization methods. Each fingerprint detects approximately 5% of the transcribed mRNAs, sampled almost independent of abundance, using inexpensive E. coli colony arrays of expressed sequence tag (EST) clones. It proved necessary to alter the differential display (DD) protocol to generate a sufficient mass of PCR products for use as a probe. The use of different oligo( dT) anchor primers with the same arbitrary primer resulted in considerable overlap among the genes sampled by each probe. This can be avoided by using different arbitrary primers with each oligo(dT) anchor primer. Four genes not previously known to be regulated by epidermal growth factor (EGF) and three genes known to be regulated by EGF in other cell types were characterized using DD fingerprints as probes for arrays. It should be possible to convert archived DD fingerprints into effective probes for arrays, allowing thousands of experiments that have already been performed to yield further information. The use of DD fingerprints as probes should increase the rate of identification of differentially regulated genes several fold while obviating the need for cloning and sequencing.